(untitled) (Sains Humanika, 2013)
The paper aims to analyse the thoughts of Imam Abu Hanifah and Imam Syafi’i on sukuk instruments. This paper is divided into two parts. The first part presents the need yet destructive forces of globalization and free trade era in today’s civilization dominated by a capitalistic system which had inadvertently caused global financial crisis and accelerated the issue on poverty, knowledge deficiency and moral decadence. These destructive forces have led to the rise of the Islamic economy concept, amongst others on the need for sukuk instruments. The discussion focuses on sukuk instrument as sukuk has an important role in free trade to fulfill the increased extraordinary economic needs of Islamic countries as well as to realize the economic needs of the entire world. The second part of the paper then analyses the legal aspects of sukuk being a subject of ongoing debate among the experts of Islamic law that seemingly has a negative tendencies on the development of sukuk. The group that rejects sukuk are influenced by the qiyas (analogical) method of Imam Syafi‘i who assumed that sukuk has the conventional elements of risk (gharar) and gambling (maisir). The group that accepts sukuk is influenced by the thoughts of Imam Abu Hanifah who assumed that sukuk is a case of individual interpretation and judgment of Islamic law that should go through the ijtihad method. It is found that both schools of thoughts in essence accepted sukuk as an Islamic financial instrument. This is because Imam Abu Hanifah relied on the istihsan method whilst when Imam Syafi‘i digressed from the qiyas method and used the takhsis theory, the resource levels of legal sources theory and the language approach theory. These theories relied by Imam Syafi’i are all in essence the istihsan theory according to Imam Abu Hanifah.